Serratia marcescens causing recurrent superficial skin infections in an immunosuppressed patient - Sarah E. Drummond; Akash Maliampurakal; Saranaz Jamdar; Lucy Melly; Susan Holmes (Wiley, 2023)
Abstract Serratia marcescens is a gram‐negative bacterium found commonly in water and soil. Initially thought to be non‐pathogenic, it is now recognised as an important cause of nosocomial and opportunistic infections. Skin infections are rare, but cases of S. marcescens causing ulcers, abscesses and necrotizing fasciitis have been reported. We report an unusual cutaneous presentation of S. marcescens in an immunosuppressed patient. A 77‐year‐old man under review for non‐melanoma skin cancer in the context of a previous cardiac transplant, presented with an asymptomatic scalp eruption. Immunosuppressive medications included ciclosporin 90 mg twice daily (2.5 mg/kg/day) and mycophenolate mofetil 1 g twice daily. Physical examination revealed well‐defined annular and polycyclic patches with brownish crusting across his scalp. Bacterial culture demonstrated a heavy growth of Staphylococcus aureus sensitive to flucloxacillin. The patient was treated with 7 days of flucloxacillin 500 mg four times daily. Despite this, the eruption extended. Skin biopsy demonstrated epidermal spongiosis, florid dermal inflammatory cell infiltrate and abundant bacteria and neutrophils in the parakeratotic crust. Fungal stains were negative as was direct immunofluorescence. Repeat culture demonstrated heavy growth of S. marcescens sensitive to ciprofloxacin. The patient was treated with 10 days of oral ciprofloxacin 500 mg twice daily along with 1% hydrogen peroxide cream topically with significant clinical improvement. Microbiological review indicated that a gram‐negative organism was present in the initial scalp swab. In addition, S. marcescens had been detected previously on a skin swab from a recent transient eruption on the torso. Further, a heavy growth of a coliform bacillus was demonstrated in a similar eruption on the chest in 2013. It was concluded that the patient was likely colonised with S. marcescens which appeared to have caused recurrent superficial skin infections over several years. We report this case to highlight an unusual clinical presentation of cutaneous S. marcescens infection. This should be considered in the differential diagnosis of skin eruptions in immunocompromised patients. Clinical information detailing a patient's immunosuppressed state must be supplied on microbiology requests to allow accurate interpretation of results, and consideration of organisms which may otherwise be overlooked or considered contaminants.